'Busy, Without Thimbles, at the Needlework': Men's Sewing and Masculinity on the Victorian Goldfields, 1851–1861. (16th January 2020) - Cramer, Lorinda
Abstract: Australia's gold-rush history has long been dominated by narratives of male adventure: of landscapes where men lived side by side, mateship took on increasing importance in the pursuit of gold, masculine behaviours and manners were emphasized and domesticity was shunned. In the early years of the rich discoveries of gold, men often travelled alone to the colony of Victoria in their search for wealth. This article examines a situation this unique environment created: where men unaccompanied by women – although women, too, were present on the diggings – were required to adopt practices perceived as feminine. It focuses in on needlework to explore the tensions that emerged given sewing was a defining female occupation during the nineteenth century, inhabiting a central place in the female experience. As this article highlights, sewing became an essential practice for men on the Victorian goldfields in order to keep themselves clothed, warm and dry. I consider how men approached their sewing tasks given needlework's inextricable link with women, and the various strategies they used to frame their sewing in letters, diaries and memoirs – sometimes for close friends and family alone, and other times for wider dissemination. Drawing on sociological frameworks on constructions of gender, masculinity and manliness, I then consider how a shifting engagement with domestic practices may have strengthened rather than challenged identity on the goldfields.